Armenian Genocide Prerequisites in Travel Memoirs (With special reference to Noel Buxton and Harold Buxton’s accounts) - Gasparyan, Naira (Armenian Folia Anglistika, 2017)
The findings of our linguocognitive research on a sound historical perspective establish a number of undeniable facts which will elucidate the situation of Armenians in Western Armenia in the pre-genocidal period.The linguistic material of Noel and Harold Buxtons’ accounts for the British Parliament, Travel and Politics in Armenia, published in 1914, has been studied with the application of a set of methods and approaches: the cognitive method of investigation combined with those of linguostylistic and linguocultural analyses on the extralinguistic basis and the method of purposive sampling. The book is an undeniable source of eyewitness facts which confirm the existing prerequisites for the 1915 Armenian genocide.
Keywords: linguocognitive; eyewitness; prerequisites; Armenian genocide; travel memoirs